Evaluating the maximal rate of lactate accumulation and estimated maximal lactate steady state in cycling - Sablain, M.; Sperlich, B.; Meixner, B.; Caen, K.; Vermeire, K.; Boone, J. (European Journal of Applied Physiology, 2025)
This study examined the reliability of the maximal rate of blood lactate (BLa-) accumulation (VLamax) and the, thereof, derived calculated power output at maximal La- steady state (cP-MLSS). Additionally, cP-MLSS was compared with the second La- thresholds determined by experts (LT2-expert), being an accurate and often used threshold concept. 13 physically active male participants (length: 182 ± 4 cm; body mass: 76.3 ± 5.8 kg) completed a step incremental protocol to determine VO2max (60.5 ± 5.8 mL·min-1·kg-1) and LT2-expert. Additionally, a 15-s isokinetic sprint test was conducted on four separate occasions to determine VLamax. cP-MLSS was calculated using a mathematical model based on VLamax, VO2max and body mass. Intraclass correlation coefficients (ICC) and coefficients of variation (CV%) were used to assess reliability. A paired sample T test was used to compare cP-MLSS (mean value of the 4 test days) and LT2-Expert. We found good reliability for VLamax (ICC = 0.80) and excellent reliability for cP-MLSS (ICC = 0.99). Moreover, LT2-expert (277 ± 41 W) and cP-MLSS (282 ± 43 W) were not significantly different. However, comparison revealed relatively wide limits of agreement (-39 to 29 W). This study concludes that VLamax and cP-MLSS are reliable measures but need further research and refinement to be used as valid parameters in training and performance contexts.